SEASONING PEDAGOGY: INCLUSION OF CULINARY APPROACHES IN LEARNING - Dharline, Varsha (PEOPLE: International Journal of Social Sciences, 2020)
Cuisine and culinary traditions are potent tools while looking at the various facets of a nation, race, community, sect, religion, class, caste or group. Culinary studies are a type of pedagogy that can help the students in understanding the nuances of a particular culture and the intricacies of their functioning respectively. It would be a more empathetic way of unraveling, learning, analyzing, evaluating, and understanding any given part of history or culture, than mere facts. In the 21st century, we aim to create a pedagogy that emphasizes global empathy and sensitivity. Culinary studies as an area of study and research are promising in its approach, wherein the universality of traditions and practices are brought to the forefront. By re-visioning, our histories from a culinary point of view we can fill in the subaltern silences about gender, sexuality, race, class, and caste. By reevaluating the role food plays in global politics, from time immemorial, we can bring in a more holistic way of assessing our past. This also aids in bringing about policies and changes that benefit the minorities, since culinary analysis promotes inclusive approaches and resolutions. In an age where gastronomical diplomacy is flourishing widely, including Culinary studies as a part of the pedagogy and using its inclusive powers would aid in raising sensitivity in humanity. Further, Cuisine goes hand in hand with various other fields of study such as science, arts, philosophy, and economics, etc., which help in promoting more interdisciplinary studies that can provide tangible results. Hence, this paper attempts to focus on the need for a conscious addition of culinary themes, devices, and perspectives in academic analysis and pedagogy.